Tax Avoidance: Peran Karakter Auditor Menekan Munculnya Tax Avoidance (Kasus Pada Perusahaan yang Tergabung dalam JII70 Tahun 2021) - Rosalina, Lisa; Hadi, Nor (AKTSAR: Jurnal Akuntansi Syariah, 2023)
The research is intended to test the effect of auditor characteristics (audit specialization, audit tenure, audit opinion and audit fees) on tax avoidance empirically. Testing this research has a fundamental essence, namely testing agency theory in the form of economic rational content in taxation so that it creates motivation to carry out tax avoidance. This research was conducted at companies that are members of the Jakarta Islamic Index (JII70) in 2021. The data is in the form of secondary data collected by documentation procedures. The total population of the study was 81 companies, the number of samples was 44 companies, and the sampling technique used was purposive sampling. To analyze the data using ordinary least squares. The results showed that two of the four hypotheses were accepted: audit specialization and audit fees significantly affected tax avoidance. However, audit tenure and audit opinion have no significant effect on tax avoidance. Observing the results of this hypothesis implies that in accordance with the rules of agency theory, economic rational strength creates tax avoidance motivation to defend the company's interests.